Patterns of 'Disorder' During the 2019 Protests in Hong Kong: Policing, Social Identity, Intergroup Dynamics, and Radicalization. (17th November 2020) - Stott, Clifford; Ho, Lawrence; Radburn, Matt; Chan, Ying Tung; Kyprianides, Arabella; Morales, Patricio Saavedra
Abstract: Across the latter half of 2019, Hong Kong became the focus of world attention as it was rocked by a wave of increasingly violent confrontations between police and protesters. Both inside and outside the Territory, several powerful political actors have argued that the paramilitary-style police interventions used to manage the protests were necessary because the disorder was being fermented by agitators. In contrast, this article explores the utility of the Elaborated Social Identity Model of crowd behaviour to help explore and explain some of the social psychological dynamics through which the 2019 protests became 'radicalised'. The article explores three key phases of their evolution to draw out the patterns of collective action and variations in policing approaches. We show that early demonstrations were focused predominantly on preventing the implementation of controversial legislation but spread and changed in form as a function of the use of crowd dispersal tactics by police. Moreover, we show how police inaction at other critical moments helped amplify perceptions of police illegitimacy that further radicalized protesters. Drawing upon a body of primary interview and secondary survey data, we also provide a social psychological analysis. We argue the observed patterns of collective action were underpinned by identity change and empowerment processes brought about as a consequence of both the structural context and the intergroup dynamics created in part by coercive policing practices.